2020
DOI: 10.1016/j.onehlt.2020.100128
|View full text |Cite
|
Sign up to set email alerts
|

Current knowledge about the antivirals remdesivir (GS-5734) and GS-441524 as therapeutic options for coronaviruses

Abstract: Recent international epidemics of coronavirus-associated illnesses underscore the urgent medical and public health need for vaccine development and regulatory body approved therapies. In particular, the current coronavirus disease 2019 (COVID-19) pandemic has quickly intensified interest in developing treatment options to mitigate impact on human life. Remdesivir (GS-5734™) is a broad-spectrum antiviral drug that is now being tested as a potential treatment for COVID-19 in international, multi-site clinical tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
181
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(192 citation statements)
references
References 37 publications
0
181
0
5
Order By: Relevance
“…RdRp is a primary target for nucleotide analog antiviral inhibitors such as Remdesivir, a drug under evaluation for SARS-CoV2 infection in clinics Imbert et al, 2006). Remdesivir, a nucleotide analog, has shown broad-spectrum antiviral activities, and preclinical studies have also shown promising human safety data (Amirian & Levy, 2020;Dong et al, 2020). Recently, a report suggested that the significant inhibition of RdRp of SARS-CoV-2 by Remdesivir, and clinical studies for the same are ongoing to evaluate the efficacy of this molecule in the COVID-19 patients (www.clinicaltrials.gov;Study No: NCT04280705).…”
Section: Introductionmentioning
confidence: 99%
“…RdRp is a primary target for nucleotide analog antiviral inhibitors such as Remdesivir, a drug under evaluation for SARS-CoV2 infection in clinics Imbert et al, 2006). Remdesivir, a nucleotide analog, has shown broad-spectrum antiviral activities, and preclinical studies have also shown promising human safety data (Amirian & Levy, 2020;Dong et al, 2020). Recently, a report suggested that the significant inhibition of RdRp of SARS-CoV-2 by Remdesivir, and clinical studies for the same are ongoing to evaluate the efficacy of this molecule in the COVID-19 patients (www.clinicaltrials.gov;Study No: NCT04280705).…”
Section: Introductionmentioning
confidence: 99%
“…Remdesivir is a monophosphoramide prodrug that is intracellularly metabolized into an adenosine analog (GS-441524) [4]. Both GS-441524 and remdesivir are metabolized into the active nucleoside triphosphate (GS-443902) by the host [5]. The adenosine nucleoside analog can inhibit viral RNA polymerases, evade proofreading by viral exonucleases, and subsequently decreases viral RNA production [4].…”
Section: Introductionmentioning
confidence: 99%
“…Coronaviruses enter host cells by binding to and fusing with cell membranes. Once inside, they subvert the host cell’s machinery to replicate, using the virus’s RNA dependent RNA polymerase (RdRp) 2. This non-structural protein is highly conserved among different strains, making it a potentially attractive drug target.…”
mentioning
confidence: 99%